(untitled) (Journal of actual problems of jurisprudence, 2019)
This article displays the legal regime of the use and ownership of land set aside for land defense feature of social relations associated with the use, possession of land defense, a long-term lease on the platform of the States on the issues of long-term changes in terms of compensated use of land defense. Keywords: Earth Defense, polygon, the legal regime of land use dolgsrochnoe vozmednoe defense.